Time to put the mammillothalamic pathway into context. (February 2021) - Dillingham, Christopher M.; Milczarek, Michal M.; Perry, James C.; Vann, Seralynne D.
Highlights: The mammillothalamic pathway plays a key role in temporal and contextual memory. The mammillothalamic pathway mediates hippocampo-cortical functions. The mammillothalamic pathway plays an important role in oscillatory co- ordination. Abstract: The medial diencephalon, in particular the mammillary bodies and anterior thalamic nuclei, has long been linked to memory and amnesia. The mammillary bodies provide a dense input into the anterior thalamic nuclei, via the mammillothalamic tract. In both animal models, and in patients, lesions of the mammillary bodies, mammillothalamic tract and anterior thalamic nuclei all produce severe impairments in temporal and contextual memory, yet it is uncertain why these regions are critical. Mounting evidence from electrophysiological and neural imaging studies suggests that mammillothalamic projections exercise considerable distal influence over thalamo-cortical and hippocampo-cortical interactions. Here, we outline how damage to the mammillary body-anterior thalamic axis, in both patients and animal models, disrupts behavioural performance on tasks that relate to contextual ("where") and temporal ("when") processing. Focusing on the medial mammillary nuclei as a possible 'theta-generator' (through their interconnections with the ventral tegmental nucleus of Gudden) we discuss how the mammillary body-anterior thalamic pathway may contribute to the mechanisms via which the hippocampus and neocortex encode representations of experience.